Effect of ultrasonic wave on vapour - liquid equilibrium of binary mixture - Ripin, Adnan; Abdul Mudalip, Siti Kholijah (Faculty of Chemical and Natural Resource Engineering, 2008)
The process of separating azeotropic mixtures is one of the challenging processes encountered in the chemical industry. Examples of typical methods used to separate azeotropic mixtures are azeotropic distillation and extractive distillation. However, these techniques are quite difficult since it require application of third component to alter the relative volatility of the mixture, α and additional separation unit to separate the third component from the product. Therefore, in this study, the effects of ultrasonic waves on vapor-liquid equilibrium (VLE) of normal binary and azeotropic mixtures were studied. The binary mixtures utilized were methanol-water and ethanol-water. Ultrasonic waves with frequency of 25 kHz, 40 kHz and 68 kHz were used. In terms of ultrasonic intensity, it was chosen from 50 to 250 W/A.cm2. Since 40 kHz is the commonly used ultrasonic frequency, the studies on the effect of different ultrasonic intensities at 50, 100, 200 and 250 W/A.cm2 to VLE of binary mixtures were done at that frequency to obtain the best ultrasonic operating intensity. Besides that, the experimental studies were also carried out using frequency of 25 kHz and 68 kHz. The results reveal that the use of ultrasonic waves altered the α, changed the VLE data of binary mixtures and consequently eliminated the azeotropic point. However, the changes were dependent on the intensity and frequency of ultrasonic wave applied. Among the frequencies studied, 25 kHz was the most suitable operating frequency for all the binary mixtures investigated. On the other hand, the best operating intensity varies, depending on the mixtures’ characteristics. The best operating intensities for methanol-water and ethanol-water mixtures were 200 and 250 W/A.cm2, respectively. The highest α values obtained in this research were 29.413 for methanol-water and 13.227 for ethanol-water. The changes in relative volatility and VLE data were caused by the cavitational activity and vacuum effect that occurred during transmission of ultrasonic wave in liquid medium. Hence, the outcome from this study verified the feasibility of using ultrasonic wave to enhance the separation of binary mixtures in distillation column and overcoming the challenges of azeotropic separation.